Tyrosine kinase inhibitors vandetanib, lenvatinib and cabozantinib modulate oxidation of an anticancer agent ellipticine catalyzed by cytochromes P450 in vitro - Kolarik, Matus; Indra, Radek; Adam, Vojtech; Heger, Zbynek; Kopeckova, Katerina; Arlt, Volker M; Stiborova, Marie (Neuro-endocrinology letters, 2019)
OBJECTIVES: Vandetanib¸ lenvatinib, and cabozantinib are tyrosine kinase inhibitors (TKIs) targeting VEGFR subtypes 1 and 2, EGFR and the RET-tyrosine kinase, thus considered as multiple TKIs. These TKIs have already been approved for treating patients suffering from thyroid cancer and renal cell carcinoma. Ellipticine, a DNA-damaging drug, is another anticancer agent that is effective against certain tumors of the thyroid gland, ovarian carcinoma, breast cancer and osteolytic breast cancer metastasis. Its anticancer efficiency is dictated by its oxidation with cytochrome P450 (CYP) and peroxidase enzymes. A number of studies testing the effectiveness of individual anticancer drugs, the pharmacological efficiencies of which are affected by their metabolism, alone or in a combination with other cytostatics demonstrated that such combination can have both positive and negative effects on treatment regimen. The aim of this study was to study the effect of vandetanib, lenvatinib and cabozantinib on oxidation of ellipticine which dictates its pharmacological efficiency. METHODS: Ellipticine oxidation catalyzed by hepatic microsomes, recombinant CYP enzymes and peroxidases (horseradish peroxidase, lactoperoxidase and myeloperoxidase) and the effect of TKIs (vandetanib, lenvatinib and cabozantinib) on this oxidation were analyzed by HPLC used for separation of ellipticine metabolites and quantification of their amounts formed during oxidation. RESULTS: The CYP enzymatic system oxidizes ellipticine up to five metabolites (9-hydroxy-, 12-hydroxy-, 13-hydroxy-, 7-hydroxyellipticine, and ellipticine N2- oxide), while peroxidases form predominantly ellipticine dimer. Ellipticine oxidation catalyzed by rat and human hepatic microsomes was inhibited by vandetanib and cabozantinib, but essentially no inhibition was caused by lenvatinib. Of individual CYP enzymes catalyzing oxidation of ellipticine, TKIs inhibited oxidation of ellipticine catalyzed by CYP2D6 > 2D1 > 2C9 > 3A1 > 3A4, the CYP enzymes participating in ellipticine oxidation to metabolites increasing the ellipticine anticancer efficiency. On the contrary, they have essentially no inhibition effect on ellipticine oxidation catalyzed by CYP1A1 and 1A2, which are the enzymes that predominantly detoxify this drug. All tested TKIs had essentially no effect on oxidation of ellipticine by used peroxidases. CONCLUSION: The results found demonstrate that TKIs vandetanib, lenvatinib and cabozantinib cause a decrease in oxidative activation of DNA-damaging drug ellipticine by several CYP enzymes in vitro which might lead to a decrease in its pharmacological efficiency. In contrast, they practically do not influence its detoxification catalyzed by CYP1A1, 1A2 and peroxidases. The present study indicates that tested TKIs seem not to have a potency to increase ellipticine anticancer efficiency.
Keywords: Oxidation-Reduction; anilidy; Phenylurea Compounds; chinoliny; oxidace-redukce; Humans; elipticiny; lidé; pyridiny; jaterní mikrozomy; Rats; zvířata; Animals; Anilides; Peroxidases; Ellipticines; Cytochrome P-450 Enzyme Inhibitors; piperidiny; Quinolines; fenylmočovinové sloučeniny; Microsomes, Liver; chinazoliny; Pyridines; Quinazolines; peroxidasy; Piperidines; krysa rodu Rattus; inhibitory cytochromu P450